Gamma and pulsed electron radiolysis studies of CyMe4BTBP and CyMe4BTPhen: Identification of radiolysis products and effects on the hydrometallurgical separation of trivalent actinides and lanthanides. (December 2021) - Schmidt, Holger; Wilden, Andreas; Modolo, Giuseppe; Bosbach, Dirk; Santiago-Schübel, Beatrix; Hupert, Michelle; Mincher, Bruce J.; Mezyk, Stephen P.; Švehla, Jaroslav; Grüner, Bohumir; Ekberg, Christian
Abstract: The radiolytic stability of the highly selective ligands CyMe4 BTBP and CyMe4 BTPhen against ionizing gamma radiation was studied in 1-octanol solution. CyMe4 BTBP and CyMe4 BTPhen are important extractants for a potential treatment of used nuclear fuel. They were studied under identical experimental conditions to directly compare the effects of gamma and pulsed electron radiolysis on the ligands and systematically study the influence of structural changes in the ligand backbone. Distribution ratios of Am 3+, Cm 3+ and Eu 3+, the residual concentration of CyMe4 BTBP and CyMe4 BTPhen in solution, and the formation of radiolysis products were studied as a function of absorbed gamma dose and presence of an acidic aqueous phase during irradiation. Quantitative and semi-quantitative analyses were used to elucidate the radiolysis mechanism for both ligands. Addition products of alpha-hydroxyoctyl radicals formed through radiolysis of the 1-octanol diluent to the ligand molecules were identified as the predominant radiolysis products. These addition products also extract trivalent metal ions, as distribution ratios remained high although the parent molecule concentrations decreased. Therefore, the utilization time of a solvent using these extractants under the harsh conditions of used nuclear fuel treatment could be considerably longer than expected. Understanding the radiolysis mechanism is crucial for designing more radiation resistant extractants. Highlights: Used nuclear fuel treatment demands very robust chemicals. Understanding the radiolysis mechanism is crucial. CyMe4 BTBP and CyMe4 BTPhen proved rather stable against irradiation. Alpha-hydroxyoctyl addition products were identified as main radiolysis products. Radiolysis mechanism showed solvated electrons to be a significant reactive species.